The Potential of Re-exports: A Probability for Fiji’s Trade Growth - Prakash, Amit; Chand, Priteshni (Asian Journal of Economics and Empirical Research, 2022)
This study investigates the significance of re-exports in Fiji. The dominance of the re-export of domestic exports is indisputable in Fiji; however, there is lack of literature concerning the performance of re-exports to total exports transiting the Fijian economy. This study aspires to fill that gap offering suggestions to strengthen the total exports of Fiji by diversifying the trade policies. Time series data is used for total exports, re-exports and domestic exports from 1985 to 2018 to establish an ARDL model. The model was subjected to diagnostic testing with a favorable outcome regarding the stability of the model for hypothesis testing. The findings re-affirm that re-exports are a significant predictor of Fiji’s total exports and trade growth. This research signifies the need for national policies to include the promotion of re-exports. Conclusively, the finding of this study is instrumental in updating or reshaping development policies for inclusive growth.